The Influence of Drawing Activities on the Performance of Fine Motoric in Children aged 5-6 Years - Nur Hafidz; Dera Puspawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Children's motor skills can be seen from the child's habit of scribbling and playing with colors. Their hands always move to write, color and draw. Based on the field observation, it is concluded that good motoric skills for children aged 5-6 years are still in the early creative classification. Thus, it is important to provide activities to strengthen the ability of the child's motor system with drawing exercises. The function of the children's drawing activity is to see whether drawing exercises affect the fine motoric performance of children aged 5-6 years. This research was conducted at the Bintang Cendekia Kindergarten in Pekanbaru. The technique used in exploration is a quantitative expressive examination via mathematical information. Given the information obtained from the results of this examination, it is found that the drawing exercises produce significant influence on the performance of the young children between pre-treatment and after-treatment phases. The results obtained from this study are that drawing exercises when carried out with confidence and the subsequent development of a creative and innovative imagination greatly impacts fine motor skills. These results can be seen from similar tests in the combined test sample table which shows alpha tally = 0.000 and alpha test = 0.05, such that alpha tally <alpha test.